Peru’s leadership in the Lima Group: emergence and failure (2015–2021) - (:unkn) unknown (Frontiers Media S.A., 2024)
This research seeks to understand the factors that enabled Peru, a medium-sized country in Latin America, to take on a leadership role in the creation and development of the Lima Group—a multilateral mechanism whose main objective was to find a resolut...
Keywords: Política exterior; Grupo de Lima